(untitled) (Estudios humanísticos. Geografía, historia y arte, 1996)
The North-west mountains in the province of León constitute a blocle due to their relatively homogeneous featores. But at the same time they have important distintive features that are faithfully reflected by each council’s economy. In this way, we find that some kinds of cattle predominate over others, or perhaps they are distributed in a different way. Both facts are related to their importance for the individuale economies of the council.